Characteristics of ferrocement sandwich aerated concrete wall elements incorporating pozzolanic waste materials - Navaz, Taha Mehman (2014)
Sandwich construction is defined as a structure that is constructed using ferrocement and aerated concrete. In contrast to the conventional concrete system, it is usually made of thin face sheets or encasement of high performance material and a thick, lightweight and low strength material as core element. Partial substitution of cement with pozzolanic materials and replacement of fine aggregate with bottom ash in this sandwich system could, be a viable strategy for reducing cement and fine aggregate consumption without impairing the performance of the system. However, the main problem of a sandwich construction is the delamination of the face sheets leading to their premature failure which is believed can be avoided by providing encasement over the core. This research focuses on the development and the characteristics of ferrocement sandwich aerated concrete wall elements by partial substitution of cement with palm oil fuel ash (POFA), pulverized fuel ash (PFA) and fine aggregate with bottom ash (BA) at varying proportions. The tests conducted involved the optimization of POFA, PFA and BA in binary and ternary cement blends in producing self-compacting and aerated concrete of desired properties for ferrocement encasement and core. In addition, the development of ferrocement encased lightweight aerated concrete sandwich wall elements as well as the investigation of strength characteristics and the durability properties were also conducted. The performance of the mixes was studied in terms of the workability, density and compressive strength. The partial replacement of cement with pozzolanic materials was done by weight in the range of 0 to 50% of the cement. Other aspects of the study included, failure mode, flexural behaviour, load-deflection behaviour, loaddeformation behaviour and load-strain behaviour. From the study, it was observed that the workability of the mixes containing POFA and PFA were significantly improved by 116%, as well as the compressive strength (93%) and unit weight by 45%. The performance of one layer wire mesh (WM) and plastic mesh (PM) showed satisfactory results in ductility and deformation. An increase of 166% (WM) and 66% (PM) for compressive were observed. At the same time, for flexure strength an increase of 39% (WM) and 95% (PM) were achieved. No delamination were found for both WM and PM wall element. In addition, the durability test on the wall elements in terms of permeability, acid attack and elevated temperature demonstrated high potentials of the specimens to be used under aggressive environment. Furthermore, the deformations of wall elements were validated with Finite element model using ANSYS software and the values predicted from the ANSYS software models were 85% - 90% accuracy compared to the experimental results. Finally, the sandwich incorporating one layer of plastic mesh can be used as a wall unit with minimum risk of delamination.